ENERGETICS OF POTENTIAL HETEROTROPHIC METABOLISMS IN THE MARINE HYDROTHERMAL SYSTEM OF VULCANO ISLAND, ITALY - Rogers K.L.; Amend J.P. (My University, 2006)
Values of overall Gibbs free energy of 144 organic oxidation (respiration) and disproportionation (fermentation) reactions are calculated at the temperatures and chemical compositions that exist in nine submarine vents, sediment seeps and geothermal wells in the hydrothermal system of Vulcano Island, Italy. The organic compounds considered here include four carboxylic acids (formic, acetic, propanoic and lactic), two C5 aldoses (arabinose and xylose), three C6 aldoses (galactose, glucose and mannose), and 15 protein-forming amino acids (Ala, Arg, Asp, Glu, Gly, His, Ile, Leu, Lys, Met, Phe, Ser, Thr, Tyr, and Val). Oxidation of these compounds is coupled to five redox pairs: O2/H2O, SO42 - / H2 S, S0/H2S, NO3- / NH4+ and Fe3O4/Fe2+. Energy yields from potential respiration reactions range from 6 to 118 kJ/mol of electrons transferred and show systematic behavior with respect to the terminal electron acceptor. Overall, respiration with O2 yields the most energy (98-118 kJ/mol e-), followed by reactions with NO3- (53- 86 kJ/mol e-), magnetite (29-91 kJ/mol e-), S0 (11-33 kJ/mol e-) and SO42 - (6-34 kJ/mol e-). Energy yields show little correlation with organic compound family, but are correlated with fluid pH. Variability in energy yields across the nine sites is greatest for Fe(III) reduction and is primarily influenced by pH and the activity of Fe2+. In addition to the potential respiration reactions, the energetics of 24 potential fermentation reactions are also calculated. As expected, fermentation reactions generally yield much less energy than respiration. Normalized to the number of moles of carbon transferred, fermentation yields-8 to 71 kJ/mol C, compared with 16 to 531 kJ/mol C for respiration reactions. All respiration and fermentation reactions, except for methionine (Met) fermentation, are exergonic under the in situ hydrothermal conditions and represent a plethora of potential metabolisms for Vulcano's diverse thermophilic heterotrophs. © 2006 Elsevier Inc. All rights reserved.